RELASI DALAM KEHIDUPAN KELUARGA PERSPEKTIF ISLAM DAN PSIKOLOGI. ANALISIS QS AT-TAHRIM AYAT 1-6 - Rufaidah; Azizah, Alfiyatul (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study analyzes Surah At-Tahrim from the perspective of spirituality and relationship psychology in Islamic family life. This surah provides guidelines for maintaining boundaries, building trust, and carrying out household responsibilities in accordance with Islamic teachings. Faith in Allah is the main factor in creating a harmonious family, while violations of established boundaries, such as lack of respect for privacy and loss of mutual trust, can trigger conflict and psychological and spiritual imbalance in the family. This study uses a descriptive analytical method with a thematic interpretation approach (maudhū‘ī). Data were collected from primary sources, namely the Qur'an and classical and contemporary interpretations, and analyzed using a relationship psychology approach. The results of the study indicate that the principles of justice, piety, and leadership based on responsibility and compassion are the main foundations in building an Islamic family. Surah At-Tahrim also presents the exemplary behavior of the Prophet Muhammad SAW in resolving household conflicts with wisdom. This study confirms that the integration of spiritual values ​​and relationship psychology in Surah At-Tahrim can be a solution in building a harmonious and faith-oriented family. The results of this study are expected to contribute to the development of a more comprehensive and applicable Islamic family concept.